A perspectiva das coisas. Raul Lino em Cascais - Rui Jorge Garcia Ramos (2011)
The perspective of things. Raul Lino in Cascais "Returning home" and Raul Lino's early training; the setting for an intellectual and architectural orientation; the picturesque and the transformation of domestic space; synthesis of a particular way of doing architecture and distortion of an ideal are the main topics addressed in this article.